Dismal outcome of t‐cell lymphoma patients failing first‐line treatment: results of a population‐based study from the Modena Cancer Registry. Issue 3 (29th April 2014) - Biasoli, Irene; Cesaretti, Marina; Bellei, Monica; Maiorana, Antonino; Bonacorsi, Goretta; Quaresima, Micol; Salati, Massimiliano; Federico, Massimo; Luminari, Stefano
Abstract: We conducted a population‐based study to establish the outcome of T‐cell lymphoma (TCL) patients failing systemic first‐line therapy. All TCL patients failing first‐line systemic therapy in the province of Modena were identified from Modena Cancer Registry between 1997 and 2010. A total of 53 patients were analysed. Regarding the type of failure, 18 patients relapsed, and 35 progressed during first treatment. Among relapsed patients, the median time from date of response to relapse after first treatment was 6.2 months (range 1.87–102). A total of 18 patients (34%) died before receiving salvage treatment, 21 received platinum or gemcitabine‐containing regimens (7 addressed to autologous stem cell transplant (ASCT)), 12 other CT regimens; 2 received radiotherapy (RT). The median survival after relapse (SAR) was 2.5 months. After a median follow‐up for living patients after failure of 35 months (range 8–111 months), 44 patients died, and the cause of death was found to be lymphoma progression in all (98%) but one of them. The median SAR was 2.5 months. The 3‐year SAR was 19%. Univariate and multivariate Cox regression analyses for SAR were performed. In multivariate analysis, performance status and type of failure were associated with a higher risk of death after relapse. The outcome of TCL patients failing first‐line therapy is poor. Only a few cases that could receive ASCT had promising chances of long remission. There is urgent need for novel agents for patients requiring second‐line treatment. Copyright © 2014 John Wiley & Sons, Ltd.